RESTATEMENT OF INDICATIONS FOR THYROID NODULES BIOPSY - Yu. K. Alexandrov; E. D. Sergeeva; A. N. Sencha (Вестник хирургии имени И.И. Грекова)
The ultrasonic signs of focal formations have a defining value for indication of fine-needle aspiration biopsy of thyroid nodules. The size and dynamics of growth aren’t so important. The evaluation of indications for performing a thyroid nodules biopsy was made in 6403 patients. It was proved that the size of thyroid nodules hadn’t any value for the indications and technique of aspiration biopsy. It was stated that a subjectivity assessment, many errors and parameters variety took place in clinical and ultrasound examination in the case of thyroid nodules changes. Indications for biopsy based on the size of nodules hadn’t any theoretical or practical value. The indications according to TIRADS system are reasonable. Their application considerably improved obtaining an informative material and increased the probability of thyroid tumor detection.